The single pseudouridine residue in Escherichia coli 16S RNA is located at position 516. - Bakin, A (1994)
The number and location of pseudouridine residues in Escherichia coli 16S ribosomal RNA has been determined by a combination of direct and indirect methods. Only one residue was found, at position 516. This site is at the 5'-end of one of the three most highly conserved long sequences of this RNA molecule. A number of experimental findings have strongly implicated this loop in the fidelity of codon recognition by A-site bound tRNA. By virtue of its location, we suggest that psi 516 may also play a role in maintaining the fidelity of protein synthesis.